Interspecific competition induces asymmetrical rooting profile adjustments in shrub-encroached open oak woodlands (Trees, 2012)
It is recognized that the extent of woody encroachment is increasing worldwide, but less is known concerning the likely altered below-ground structure of cooccurring plants. The aim of this study was to analyze the root system plasticity of three layers of vegetation growing together (trees, shrubs and pasture) and identify potential mechanisms of competition avoidance. Root morphology and distribution of trees, pasture and two contrasting shrub species (deep and shallow rooted) were studied in open oak woodlands of south-western Spain. Soil samples were obtained from paired adjacent plots, with and without shrubs, by taking soil cores to a depth of 3 m. Analysis of tree and pasture root systems in the presence of shrubs revealed signiﬁcant reductions in root biomass and consistent increases in speciﬁc root length. Additionally, root proﬁles changed substantially, becoming signiﬁcantly deeper for trees and shallower for pasture. In contrast, both types of shrub increased their root biomass when growing in competition, but without signiﬁcantly modifying their rooting proﬁle. Shrubs seem to be stronger competitors for below-ground resources than neighboring species. However, trees and pasture show clear plastic responses to shrub presence, irrespective of their rooting patterns, probably to minimize competitive interactions and maximize resource acquisition.